2004
DOI: 10.1038/nature03148
|View full text |Cite
|
Sign up to set email alerts
|

The role of barren stalk1 in the architecture of maize

Abstract: The architecture of higher plants is established through the activity of lateral meristems--small groups of stem cells formed during vegetative and reproductive development. Lateral meristems generate branches and inflorescence structures, which define the overall form of a plant, and are largely responsible for the evolution of different plant architectures. Here, we report the isolation of the barren stalk1 gene, which encodes a non-canonical basic helix-loop-helix protein required for the initiation of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
298
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 327 publications
(311 citation statements)
references
References 29 publications
8
298
0
5
Order By: Relevance
“…The two QTL for ears per plant detected in the Mo17 backcross in Stuber et al (1992) mapped around the QTL for ear per plant on chromosomes 7 and 8 in our study. Finally, the barren stalk1 locus, at which mutant alleles can eliminate the production of female inflorescenses (Gallavotti et al, 2007), is located near the major barrenness and yield QTL on chromosome 3, suggesting that this locus may also contribute to natural variation for barrenness in maize. Overlapping QTL in barrenness and grain yield suggest possible genetic mechanisms for carbon allocation as may be expected ).…”
Section: Discussionmentioning
confidence: 99%
“…The two QTL for ears per plant detected in the Mo17 backcross in Stuber et al (1992) mapped around the QTL for ear per plant on chromosomes 7 and 8 in our study. Finally, the barren stalk1 locus, at which mutant alleles can eliminate the production of female inflorescenses (Gallavotti et al, 2007), is located near the major barrenness and yield QTL on chromosome 3, suggesting that this locus may also contribute to natural variation for barrenness in maize. Overlapping QTL in barrenness and grain yield suggest possible genetic mechanisms for carbon allocation as may be expected ).…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence suggests that it is possible and even probable for some loci to show high levels of differentiation (or reduced within population variation) without having been targets of selection either owing to chance alone, or for instance, due to incorrect models of demographic history used in estimating parameters like F ST (e.g., island versus stepping stone models; see Akey et al, 2004) or ascertainment bias (Thornton and Jensen, in press). Similarly, it is also possible for loci to be under selection without yielding statistically significant results in tests for selection (Gallavotti et al, 2004;McVean et al, 2005;Przeworski et al, 2005;Teshima et al, 2006). Simulation studies by Teshima et al (2006) suggest that a sizable proportion of loci under selection will be missed in empirical genome-wide scans, especially if the loci selected had previously been neutral.…”
Section: Limitations Of Population Genomicsmentioning
confidence: 99%
“…Yeast two-hybrid screening with PID identified calciumbinding proteins that act upstream of PID (Benjamins et al, 2003). In contrast, a yeast two-hybrid screen with BIF2 identified BARREN STALK1 (BA1), a nuclear localized basic helix-loop-helix putative transcription factor as an interacting partner with BIF2 (Gallavotti et al, 2004;Skirpan et al, 2008). In vitro kinase assays showed that BIF2 phosphorylates BA1 (Skirpan et al, 2008).…”
Section: Role Of Auxin In Axillary Meristem Initiation During Vegetatmentioning
confidence: 99%